Efficacy and Safety of Insulin Pump During the Fasting Month of Ramadan among Patients in Libya - Nadia Alghazir; Ebtisam Hadeed; Omalmeer Gadaffi; Faten BenRajab; Miludda Alhmady (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Insulin pump has proved to be an effective way to administer insulin in patient with type 1 diabetes mellitus and it's the most effective way to control blood glucose level with the lowest rate of hypoglycemia. However, no data are available to assess its efficacy and safety in fasting diabetics. The present study aims to assess the efficacy and safety of insulin pump during fasting in Ramadan. Methods. This was a prospective observational single center non randomized study. Patients with type I diabetes who received insulin through insulin pump (n= 21). Variables such as, weight changes, biochemical profile, HbA1c, and lipid profile were evaluated before and after Ramadan. Results. Most patients on insulin pump were able to complete their fasting during Ramadan (average 2 fast breaking per patient)) with minimal episodes of hypoglycemia and severe hyperglycemia requiring hospitalization. No significant difference was found in biochemical profiles of patients on insulin pump who were fasting during the month of Ramadan as compared to pre-Ramadan. Conclusion. The insulin pump proved to be effective and safe in fasting patient during Ramadan in Libya.